Managing Triads in a Military Avionics Service Maintenance Network in Taiwan - Peng, Tzu-Ju Ann; Lin, Nan-Juh; Martinez, Veronica; Yu, Chow-Ming Joseph (Emerald Group Publishing Limited, 2010)
Purpose – The purpose of this paper is to investigate how different types of triad structures, and the management mechanisms adopted by the focal company, affect cooperative performance. Design/methodology/approach – This paper uses a social network perspective to examine the triad management phenomenon in the military avionics maintenance context, which is closely associated with the field of operations management. Findings – This paper demonstrates that different triad structures and management mechanisms influence perceived cooperative performance. Four main findings emerged: in a triad, a firm playing a bridging role perceives higher cooperative performance than when playing a peripheral role in the triad or being located in a fully connected triad. When a firm plays the bridging role in a triad, and has a high level of trust, this leads to higher perceived cooperative performance. When a firm plays a peripheral role in a triad, high levels of coordination mechanism combined with high levels of trust result in higher levels of perceived cooperative performance. In a fully linked triad, when the coordination mechanism is well developed, the level of trust is high, so that the resulting level of perceived cooperation is high. Originality/value – This paper extends the knowledge of triad management by providing an in-depth study of a well-defined network setting with exceptionally high-level access to the most senior executives. In practice, this paper shows how to manage different
Keywords: Aerospace industry; Maintenance programmes; Supply chain management; Taiwan